Morfometrik Ayam Broiler dengan Pemeliharaan Intensif dan Akses Free Range di Daerah Tropis - Rahayu H. S., I.; Darwati, S.; Mu'iz, A. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
Broiler developed to produce meat in a fast manner. Generally, broiler reared by intensive system. Rearing system can be split into two kinds, intensive and free-range rearing system. The aim of this research was assessing the morphometric size of male and female broiler which are raised under intensive and free-range systems. Rearing systems was not have influence on the morphometric size of the chicken except in the length of the tibia, femur, and wing on the third week. Sex have real impact on the length of shank, tibia, wings, femur, and chest circumference, and also significantly affect the width and depth of the chest, neck, and spine lenght in fifth week. Rearing systems both intensive and free-range produced same frame size on broiler chicken.